The Participles in Manuk Abeghyan’s «Grammar of Grabar» - Shahverdyan, Tereza (Bulletin of Yerevan University B: Philology, 2026)
The present study is devoted exclusively to Manuk Abeghyan’s interpretation of Classical Armenian (Grabar) participles. The research examines the morphological characteristics of participles and, where necessary, addresses their syntactic functions, since Abeghyan occasionally considered these issues as well. Over a century has passed since the publication of Abeghyan’s Grammar of Grabar, and numerous extensive studies proposing new approaches have appeared in the meantime. For this reason, the present work also takes into account more recent scholarly opinions, offering a comprehensive review of the current academic discourse. In particular, the Grabar future participle with the suffix -ots is dependent in nature and functions exclusively within compound tense forms of the indicative and subjunctive moods, lacking independent usage. This contrasts with the past participle, which is semi-independent. However, Abeghyan’s grammar provides examples in which the -ots future participle appears to function independently; we believe that in such cases it has been confused with the oblique case form of the past participle, requiring further clarification. In Abeghyan’s treatment of the future participle, no mention is made of the -i variant, which is instead discussed under the present-subjunctive participle. Although Grabar texts indeed contain instances where this form is used with a present-subjunctive meaning, it is predominantly a future participle with independent usage. The four Grabar participles—the indefinite, the present (or subjunctive), the future, and the past—have largely preserved their core participial meanings and word-formation characteristics, albeit with certain morphological and semantic modifications across historical periods. Taken as a whole, Manuk Abeghyan’s Grammar of Grabar has not lost its relevance to this day and remains one of the most important foundational sources for the scientific description of Classical Armenian grammar. Its enduring value lies in its detailed analysis and systematic presentation, which continue to inform contemporary linguistic research.